Answer:
Step-by-step explanation:
some rules of logarithmic function
[tex]ln(a) - ln(b)=ln(\frac{a}{b})[/tex]
[tex]e^{ln(a)}=a[/tex]
[tex]ln(a)^{n}=nln(a)[/tex] vice-versa [tex]nln(a)=ln(a)^{n}[/tex]
If ㏑(a) = ㏑(b), then a = b
∴ [tex]2ln(e^{ln(2x)})-ln(e^{ln(10x)})=ln(30)[/tex]
Use the 2nd rule to simplify it
[tex]e^{ln(2x)}=2x\\e^{ln(10x)}=10x\\[/tex]
2㏑(2x) - ㏑(10x) = ㏑(30)
Use the 3rd rule in the 1st term
∵ 2㏑(2x) = ㏑(2x)² = ㏑(4x²)
∴ ㏑(4x²) - ㏑(10x) = ㏑(30)
- Use the 1st rule with the left hand side
[tex]ln(4x^{2})-ln(10x)=ln(\frac{4x^{2}}{10x})\\\\ln(\frac{4x^{2}}{10x})=ln(30)\\\\ \frac{4x^{2}}{10x}=\frac{2x}{5}=\frac{2}{5}x\\\\ ln(\frac{2}{5}x)=ln(30)[/tex]
Use the 4th rule
[tex]\frac{2}{5} x = 30[/tex]
Multiply both sides by 5
∴ 2 x = 150
- Divide both sides by 2
∴ x = 75
The value of x = 75